Skin comfort of base layer wool garments. Part 3: The effect of ethnicity on perceptions of comfort using Chinese and Australian wearers. Issue 11 (July 2015) - Speijers, Jane; Stanton, John H; Naylor, Geoffrey RS; Ramankutty, Padmaja; Tester, David
There is commercial interest in designing wool next-to-skin garments specifically for the domestic Chinese market. However, the current understanding of comfort has largely been obtained from studies with Caucasian wearers and its applicability to Chinese wearers is unknown. A study was undertaken that examined the tactile, thermal and moisture-based sensations of two groups of untrained female wearers drawn from an urban population in Australia: 25 Chinese wearers who had been born in China to Chinese parents and 23 control wearers. Sensations were recorded during a series of activities in a range of controlled climatic environments while wearing next-to-skin garments made from different fiber types (wool and cashmere) and different fiber diameters (15.5–20.3 µm). There is no evidence from this experiment to conclude that Chinese wearers are more sensitive in their discomfort, prickle and scratch response than the control wearers. They recorded lower scores and smaller increases in scores in response to activity, environment and garment type than the control wearers. For sensations that relate to the feel of garments against the skin, the Chinese group experienced increased sensation in comparison to the control group during a range of motion activities, for the 20.3 µm wool garment only. For sensations that relate to the thermophysiological state of the body, the control group experienced increased sensation as temperature and activity rose in comparison to the Chinese group. These differences in the sensational responses to activity and environment were associated with similar responses in discomfort scores.